Evaluation of the susceptibility of neurons and neural stem/progenitor cells derived from human induced pluripotent stem cells to anticancer drugs - Hayato Fukusumi; Yukako Handa; Tomoko Shofuda; Yonehiro Kanemura (Elsevier, 2019)
Various chemicals, including pharmaceuticals, can induce acute or delayed neurotoxicity in humans. Because isolation of human primary neurons is extremely difficult, toxicity tests for these agents have been performed using in vivo or in vitro models. Human induced pluripotent stem cells (hiPSCs) can be used to establish hiPSC-derived neural stem/progenitor cells (hiPSC-NSPCs), which can then be used to obtain hiPSC-neurons. In this study, we differentiated hiPSC-NSPCs into neurons and evaluated the susceptibility of hiPSC-neurons and parental hiPSC-NSPCs to anticancer drugs in vitro by ATP assay and immunocytostaining. The hiPSC-neurons were more resistant to anticancer drugs than the parental hiPSC-NSPCs. In the toxicity tests, high-dose cisplatin reduced the levels of ELAVL3/4, a neuronal marker, in the hiPSC-neurons. These results suggest that our methodology is potentially applicable for efficient determination of the toxicity of any drug to hiPSC-neurons. Keywords: Human induced pluripotent stem cell, Neural stem/progenitor cell, Neuron, Anticancer drug, Toxicology